Factors Affecting Employment in Manufacturing Industries of Iran - Mansour Asgari (مجله توسعه و سرمایه, 2021)
Objective: This article seeks to identify the factors affecting employment in Iran's manufacturing industries during the period 1996-2015. Employment is one of the main channels affecting the performance of the economy, the changes of which will affect production, imports, exports, competition, and investment.Considering that the manufacturing industry plays an important role in creating value-added and job creation in the country's economy, this issue has caused every part of the country's manufacturing industry to be associated with high diversity. In recent years, factory industries have experienced many fluctuations due to the domestic and international conditions governing the country's economy, which has caused the major industries of the country to operate with less than production capacity, despite the high installed capacity.   Method: Employment and factors affecting macroeconomic factors creating new job opportunities and increasing employment is one of the most important issues for economic planners and policymakers. Identifying the factors affecting employment is one of the most important issues in the Iranian economy.   Results: In the long run and in the classical model of labor demand, the wage variable has an important role in determining the equilibrium level of employment; in addition, the variables of firm production are also effective in determining the level of employment. On the other hand, in the long run, the main factors affecting the demand for employment in the manufacturing industry are wage, output, and capital utilization variables, which can be replaced by capital stock, which is also interpreted as the substitution effects of scale. To extract the labor demand function, there are several methods by which labor demand is extracted under the same conditions. In this study, to extract the labor demand in 22 industrial sectors with 10 employees and more, we use the method presented by Varian (1978). In this method, the labor demand function can be minimized by reducing the cost function to the production function.   Conclusion: The purpose of this paper is to analyze the factors affecting employment in the manufacturing industry by dividing the two-digit ISIC codes by dividing the two-digit ISIC codes by 10 employees and moreover, the period 1996-2015 using a generalized panel data approach and Generalized Least Squares (GLS) estimator. The most important factor in the development of employment in manufacturing industries is the increase in production, the realization of which requires the coordination of monetary, fiscal, foreign exchange and trade policies, and extensive interaction with the global economy and attracting foreign direct investment. The results show that the elasticity of employment demand with respect to wages, production, and capital stock are -0.22, 0.58, and 0.12, respectively. Considering that one of the effective factors in increasing employment in Iran's manufacturing industries are increasing production, it is recommended that the government place more emphasis on combating the smuggling of goods and developing a competitive environment to expand industrial activities and ultimately increase demand for industrial products. Increase industrial production and thereby increase labor demand. Considering the positive effect of capital stock on employment in the manufacturing industries, it is recommended to adopt policies to increase employment, which will lead to increased investment in factory industries to increase employment by increasing capital stock.       Objective: This article seeks to identify the factors affecting employment in Iran's manufacturing industries during the period 1996-2015. Employment is one of the main channels affecting the performance of the economy, the changes of which will affect production, imports, exports, competition, and investment.Considering that the manufacturing industry plays an important role in creating value-added and job creation in the country's economy, this issue has caused every part of the country's manufacturing industry to be associated with high diversity. In recent years, factory industries have experienced many fluctuations due to the domestic and international conditions governing the country's economy, which has caused the major industries of the country to operate with less than production capacity, despite the high installed capacity. Method: Employment and factors affecting macroeconomic factors creating new job opportunities and increasing employment is one of the most important issues for economic planners and policymakers. Identifying the factors affecting employment is one of the most important issues in the Iranian economy. Results: In the long run and in the classical model of labor demand, the wage variable has an important role in determining the equilibrium level of employment; in addition, the variables of firm production are also effective in determining the level of employment. On the other hand, in the long run, the main factors affecting the demand for employment in the manufacturing industry are wage, output, and capital utilization variables, which can be replaced by capital stock, which is also interpreted as the substitution effects of scale. To extract the labor demand function, there are several methods by which labor demand is extracted under the same conditions. In this study, to extract the labor demand in 22 industrial sectors with 10 employees and more, we use the method presented by Varian (1978). In this method, the labor demand function can be minimized by reducing the cost function to the production function.       Conclusion: The purpose of this paper is to analyze the factors affecting employment in the manufacturing industry by dividing the two-digit ISIC codes by dividing the two-digit ISIC codes by 10 employees and moreover, the period 1996-2015 using a generalized panel data approach and Generalized Least Squares (GLS) estimator. The most important factor in the development of employment in manufacturing industries is the increase in production, the realization of which requires the coordination of monetary, fiscal, foreign exchange and trade policies, and extensive interaction with the global economy and attracting foreign direct investment. The results show that the elasticity of employment demand with respect to wages, production, and capital stock are -0.22, 0.58, and 0.12, respectively. Considering that one of the effective factors in increasing employment in Iran's manufacturing industries are increasing production, it is recommended that the government place more emphasis on combating the smuggling of goods and developing a competitive environment to expand industrial activities and ultimately increase demand for industrial products. Increase industrial production and thereby increase labor demand. Considering the positive effect of capital stock on employment in the manufacturing industries, it is recommended to adopt policies to increase employment, which will lead to increased investment in factory industries to increase employment by increasing capital stock.